THE EFFECT OF AMBON BANANA (MUSA PARADISIACA) ON PREGNANT WOMEN WITH HYPERTENSION IN THE WORK AREA UPTD CIRINTEN HEALTH CENTER, LEBAK DISTRICT - Lastriyani, Lastriyani; Tahun, Omega Dr. (HEARTY, 2024)
Background Hypertension is a disease that can attack anyone from the youngest to the oldest and do not look at the rich or poor. Woman pregnant with hypertension have risk tall caught complications Which heavy like disease heart, disease vessels brain blood, or fail organ until death. Hypertension treatment includes non pharmacology, namely treatment relatively cheap And No has significant side effects compared to pharmacological drugs and has caused many people to look again at traditional medicinal plants including fruits For overcome hypertension include Ambon banana. Research purposes. The aim of the research is to determine the effect of Ambon banana (Musa Paradisiaca) towards pregnant women with hypertension in the UPTD Puskesmas working area Cirinten Lebak Regency. Research method This research is a type of quantitative research, with the research design used being Quasi Experimental with approach pretest posttest one groups design, The sample for this research was 20 people. Research result There is a difference in the mean value before and after consumption banana ambon (Moses Paradisiaca) namely systolic before the mean value 145.4, and after that 123.4 whereas For mark pressure diastolic blood with the mean value 97.0 and after that 87.2, while the Paired t-test showed that there was a significant effect of Ambon banana (Musa Paradisiaca) on pregnant women with hypertension in the working area of the UPTD of the Cirinten Health Center, Lebak Regency. Conclusions and recommendations. Efforts to treat hypertension include providing non-pharmacological therapy to hypertensive patients and monitoring so that hypertensive patients' compliance with non-pharmacological therapy can be controlled.